PSYCHOLOGICAL WELL-BEING PADA SINGLE PARENT MOTHERYANG DITINGGAL SUAMINYA MENINGGAL DUNIA - HASANAH, USWATUN; , Santi Sulandari, S.Psi., M.Ger (2016)
Single parent mother who was left by the passed away of her husband needs approximatley nine monts until two years to recover her sadness. Single parent mother will face the difficulties case such as economic, the lost of life desire and weak of self confidence. Single parent mother who was psychological well-being will try to advance her life by working, treating the child and social effort. The objective of the study is focus on understanding and describing the psychological well-being condition of single parent mother after she had left by her husband. Ther are five sources based on parposive sampling with the age characteristic 20-50 year minimal, her husband had pass away 0-4 years gap, and she had no job when herhusband alive. The result of the study has proved that the single parent mother with psychological well-being is taster in accepting the reality. Tham who has not, and able to advance her husband responsibility in the family, good social relationship and also aktive in society activities. Single parent mother who had left by her husband has no desive to married untill they succes. In another way single paren mother want to expand her. Exertion in order to has a self-reliant.